Microbiological evaluation of some Egyptian fermented dairy products - AMAN, I.M.; AL-HAWARY, I.I.; ELEWA, S.M.; EL-KASSAS, W.M.; EL-MAGD, M.A. (Journal of the Hellenic Veterinary Medical Society, 2021)
This study was carried out to evaluate the microbiological quality of plain and fruit yoghurt and rayeb. Sixty samples of yoghurt (30 plain &30 fruit) and 60 samples of rayeb (30 plain &30 fruit) were randomly collected from different supermarkets in Kafr El-Sheikh city. The obtained results revealed that the pH values of plain and fruit yoghurt were significantly higher than those of plain and fruit rayeb. Staphylococcus aureus counts were 4.33×102 ± 0.42×102 and 4.0×102 ±0.57×102cfu/g, in fruit yoghurt and plain rayeb, respectively. Only two samples of plain yoghurt and fruit rayeb contained S.aureus with counts of 9.0x 102±1.0×102 and 1.1×103± 0.1×103cfu/g, respectively. Coliforms were only detected in plain and fruit yoghurt with counts of 8.82×104 ± 0.81×104 and 5.4×10 ± 1.04×10 cfu/g, respectively. E.coli was isolated from plain and fruit yoghurt with incidence rates of 73.3 and 6.7%, respectively. All E.coli isolates from plain yoghurt were serologically identified as, O91: H21, O26: H11, O121: H7, O163: H2, O114: H4, O128: H2 O111: H2, and O86. Fruit yoghurt had only O111:H2. Yeast and molds were also found in the four dairy products with high frequencies for Penicillium species.The two virulence genes, enterotoxin gene A and Shiga toxins 2, were detected in three isolates of S. aureus and E. coli by multiplex PCR. With these results, we could conclude that yoghurt and rayeb samples collected from Kafr El-Sheikh city supermarkets create a health threat to consumers. Therefore, the application of hygienic measures and sanitary practicesis necessary to produce high-quality fermented products to assure consumer’s safety.